Interaction of Background Noise and Auditory Hallucinations on Phonemic Mismatch Negativity (MMN) and P3a Processing in Schizophrenia - Francis, Ashley M.; Knott, Verner J.; Labelle, Alain; Fisher, Derek J. (Frontiers in Psychiatry, 2020)
Auditory hallucinations (AH) are among the cardinal symptoms of schizophrenia (SZ). During the presence of AHs aberrant activity of auditory cortices have been observed, including hyperactivation during AHs alone and hypoactivation when AHs are accompanied by a concurrent external auditory competitor. The present study aimed to explore whether background noise altered the auditory mismatch negativity (MMN) and P3a in those with SZ and treatment-resistant AHs. Methods : MMN and P3a were assessed in 12 hallucinating patients (HP), 11 non-hallucinating patients (NP) and 9 healthy controls (HC) within an auditory oddball paradigm. Standard (P = 0.85) and deviant (P = 0.15) stimuli were presented during three noise conditions, silence (SL), traffic noise (TF) and wide-band white noise (WN). Results: HPs showed significantly greater deficits in MMN amplitude relative to NPs in all background noise conditions, though predominantly at central electrodes. Conversely, both NPs and HPs exhibited significant deficits in P3a amplitude relative to HCs under the silence condition only. Significance: These findings suggest that the presence of AHs may specifically impair the MMN, while the P3a appears to be more generally impaired in schizophrenia. That MMN amplitudes are specifically reduced for HPs during background noise conditions suggests HPs may have a harder time detecting changes in phonemic sounds during situations with external traffic or ‘real-world’ noise compared to NPs.